Yearbook of the European Convention on Human Rights - Council of Europe Staff. author. aut Link
XVI, 697 p.
Keywords: This Volume contains the Report of the European Commission of Human Rights on the "Greek Case" (Applications No. 3321/67, Den mark v. Greece; No. 3322/67, Norway v. Greece; No. 3323/67, Sweden v. Greece; No. 3344/67, Netherlands v. Greece) and the Resolution DH (70) 1 adopted by the Committee of Ministers of the Council of Europe on 15 April 1970 relating to this case. These four applications, which were filed with the Commission of Human Rights in September 1967, alleged that the Greek Government which had come into power in April of that year had violated its obliga tions under the European Convention on Human Rights. They referred to the suspension of certain articles of the Greek Constitution and other legislative measures and administrative practices; they alleged that, re gardless of any individual or specific injury, these acts affected the cor responding Articles of the Convention on Human Rights. The Applicant Governments also submitted that the derogation made by the Greek Government under Article 15 of the Convention (which permits a government to take measures derogating from its obligations under the Convention in time of war or public emergency) was not justified. The Commission on 2 October 1967, decided to give priority to these cases and, after hearing the submissions of the parties on 23 and 24 January 1968, it declared the applications admissible on 24 January 1968. The decision on admissibility was published in this Yearbook Vol. 11, pages 690 to 728.